School Bullying Experienced by Chinese Migrant Children in Urban Schools and Its Intervention Strategies - Jingya Wang (Art and Society, 2024)
China’s migrant children face major challenges in moving from rural areas to cities, of which the most important concern is discrimination and bullying. This article discusses the problem of school bullying encountered by migrant children and emphasizes the negative impact of this phenomenon on their body and mind. This article also applies the principle of design justice, and proposes self-protection measures and community-based intervention strategies for migrant children to reduce the occurrence of bullying and create a safer and more inclusive environment.